Developing Entrepreneurial Competencies in Multicultural Teams: An Evaluation of the ECMT+ Educational Model (European Journal of Marketing and Economics, 2025)
This study evaluates the effectiveness of multicultural entrepreneurship education through the Erasmus+ ECMT+ (Entrepreneurship and Communication in Multicultural Teams) program. As globalization intensifies, higher education must equip students with both entrepreneurial competencies and intercultural collaboration skills. The research examines learning outcomes from a two-week intensive program involving 48 participants from 14 countries across 7 European institutions, hosted at Karelia University. Using a mixed-methods approach combining pre/post quantitative surveys (N=48) and qualitative analysis of reflective essays (N=32), we assess three key dimensions: (1) development of entrepreneurial mindsets, (2) intercultural team dynamics, and (3) application of innovative teaching methodologies. Results indicate significant improvements in entrepreneurial self-efficacy (72% of participants), with 85% reporting enhanced ability to navigate cultural differences in business contexts. The study identifies four success factors: project-based learning in diverse teams, structured reflection exercises, real-world business challenges, and digital collaboration via the Claroline Connect platform. Our findings contribute to the design of effective multicultural entrepreneurship education by demonstrating how experiential learning in culturally diverse teams accelerates the development of crucial twenty-first century skills. The paper concludes with recommendations for optimizing similar programs and a proposed framework for assessing intercultural entrepreneurial competencies.
Keywords: Entrepreneurship education, intercultural competence, multicultural teams, experiential learning, Erasmus+, entrepreneurial mindset, higher education innovation, collaborative learning